Adhesive Interactions Between Lactic Acid Bacteria and β-Lactoglobulin: Specificity and Impact on Bacterial Location in Whey Protein Isolate - Gomand, Faustine; Borges, Frédéric; Guerin, Justine; El-Kirat-Chatel, Sofiane; Francius, Gregory; Dumas, Dominique; Burgain, Jennifer; Gaiani, Claire (Frontiers in Microbiology, 2019)
In the last decade, there has been an increasing interest in the potential health effects associated with the consumption of lactic acid bacteria (LAB) in foods. Some of these bacteria such as Lactobacillus rhamnosus GG (LGG) are known to adhere to milk components, which may impact their distribution and protection within dairy matrices and therefore is likely to modulate the efficiency of their delivery. However, the adhesive behavior of most LAB, as well as its effect on food structuration and on the final bacterial distribution within the food matrix remain very poorly studied. Using a recently developed high-throughput approach, we have screened a collection of 73 LAB strains for their adhesive behavior toward the major whey protein β-lactoglobulin. Adhesion was then studied by genomics in relation to common bacterial surface characteristics such as pili and adhesion-related domain containing proteins. Representative adhesive and non-adhesive strains have been studied in further depth through biophysical measurement using atomic force microscopy (AFM) and a relation with bacterial distribution in whey protein isolate (WPI) solution has been established. AFM measurements have revealed that bacterial adhesion to β-lactoglobulin is highly specific and cannot be predicted accurately using only genomic information. Non-adhesive strains were found to remain homogeneously distributed in solution whereas adhesive strains gathered in flocs. These findings show that several LAB strains are able to adhere to β-lactoglobulin, whereas this had only been previously observed on LGG. We also show that these adhesive interactions present similar characteristics and are likely to impact bacterial location and distribution in dairy matrices containing β-lactoglobulin. This may help with designing more efficient dairy food matrices for optimized LAB delivery.